2010
DOI: 10.1021/ma902203r
|View full text |Cite
|
Sign up to set email alerts
|

Smart “All Acrylate” ABA Triblock Copolymer Bearing Reactive Functionality via Atom Transfer Radical Polymerization (ATRP): Demonstration of a “Click Reaction” in Thermoreversible Property

Abstract: Tailor-made ABA triblock copolymers (poly(furfuryl methacrylate)-b-poly(2-ethylhexyl acrylate)-b-poly(furfuryl methacrylate) (FEF)) bearing a reactive pendant furfuryl group were successfully synthesized by atom transfer radical polymerization. The chemical compositions were calculated by 1H NMR, and molecular weights and molecular weight distributions were determined by gel permeation chromatography analysis. The tensile properties of the triblock copolymers such as tensile strength, elongation at break, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 59 publications
7
101
0
Order By: Relevance
“…In our previous work the DSC measurements and the self-healing studies of the copolymers P(AMA-co-FMA-co-MIMA) revealed that the variation of the chain length of the co-monomers influenced the temperature of the retro-Diels-Alder reaction: More nonpolar environments resulted in higher temperatures of the retro-Diels-Alder reaction [20]. This effect was also observed by Kavitha and Singha [16][17][18][19]. Additional, other studies revealed that more polar environments of the maleimide/furan unit resulted in a slightly decreased rDA temperature [25][26][27][28].…”
Section: A N U S C R I P Tsupporting
confidence: 56%
See 1 more Smart Citation
“…In our previous work the DSC measurements and the self-healing studies of the copolymers P(AMA-co-FMA-co-MIMA) revealed that the variation of the chain length of the co-monomers influenced the temperature of the retro-Diels-Alder reaction: More nonpolar environments resulted in higher temperatures of the retro-Diels-Alder reaction [20]. This effect was also observed by Kavitha and Singha [16][17][18][19]. Additional, other studies revealed that more polar environments of the maleimide/furan unit resulted in a slightly decreased rDA temperature [25][26][27][28].…”
Section: A N U S C R I P Tsupporting
confidence: 56%
“…The first investigations on the synthesis of PFMA via ATRP and free radical polymerization (FRP) and the copolymerization with methyl methacrylate (MMA) were published by Kavitha and Singha as well as the synthesis of a PFMA-b-PEHA-b-PFMA triblock copolymer. The authors also studied the self-healing properties of the copolymer [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, at higher frequency range, the stress applied to polymers is too fast for molecular rearrangement, and thus flow becomes restricted, resulting in higher mechanical strength. Similar observation has been observed for ATRP synthesized typical ABA triblock copolymer [25]. The 61% syndiotactic triblock copolymer (Figure 4-b) exhibited higher mechanical strength (G') compared to 80% syndiotactic one due to larger polystyrene block (Figure 4-a).…”
Section: Figsupporting
confidence: 84%
“…The G'' values of 80% syndiotactic polymer was considerably higher than 61% syndiotactic one ( Figure 6). The lower values of G'' in the lower frequency range of the sample supported more molecular relaxations as was observed by Kavitha et al [25]. A continuous increase in G'' as frequency increased from 0.1 to 10 Hz has been attributed by restricted flow behavior in limited time frame that hindered the molecular relaxation depending upon applied temperature.…”
Section: Figsupporting
confidence: 77%
“…[56][57][58] The cycloaddition of furan and maleimide groups (forward DA reaction) proceeds at temperatures lower than ca 100 1C, whereas the retro DA reaction for the depolymerization becomes dominant at higher temperatures. The equilibrium control between the forward DA and retro DA reactions is workable in both solution and bulk state.…”
Section: Thermoreversible Crosslinking-decrosslinking Polymersmentioning
confidence: 99%